Life expectancy and old age savings - Mariacristina De Nardi; Eric French; John Bailey Jones (Federal Reserve Bank of Chicago, 2009)
Rich people, women, and healthy people live longer. We document that this heterogeneity in life expectancy is large, and we use an estimated structural model to assess its effect on the elderly's saving. We find that the differences in life expectancy related to observable factors such as income, gender, and health have large effects on savings, and that these factors contribute by similar amounts. We also show that the risk of outliving one's expected lifespan has a large effect on the elderly's saving behavior.
Keywords: 330; Alte Menschen; Vermögen; Gesundheit; Alterssicherung; Sparen; USA